1961
DOI: 10.2105/ajph.51.5.706
|View full text |Cite
|
Sign up to set email alerts
|

Primary Antirabies Immunization of Man with HEP Flury Virus Vaccine

Abstract: The circumstance that rabies is potentially an increasing threat to certain population groups has led to efforts to develop a safe means for primary immunization. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1962
1962
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…In laboratory experiments, however, immunized red foxes, grey foxes, and dogs with titres greater than 1: 5 but less than 1: 125 generally survive even severe challenge; even animals with titres less than 1: 5 have resisted challenge; (Dean, Evans & Thompson 1964;Schmidt & Sikes 1968;Black & Lawson 1970). Neutralizing antibody in apparently healthy animals has been attributed to incipient disease, acute, chronic, abortive, subclinical, or latent infections (Ruegsegger, Black & Sharpless 1961;Bell 1966Bell , 1975, localized (intramuscular) replication of the virus (Baer 1975b), ingestion of infected material (Ramsden & Johnston 1975), or bite exposure (Serokowa 1969).…”
Section: Immune Responsementioning
confidence: 99%
“…In laboratory experiments, however, immunized red foxes, grey foxes, and dogs with titres greater than 1: 5 but less than 1: 125 generally survive even severe challenge; even animals with titres less than 1: 5 have resisted challenge; (Dean, Evans & Thompson 1964;Schmidt & Sikes 1968;Black & Lawson 1970). Neutralizing antibody in apparently healthy animals has been attributed to incipient disease, acute, chronic, abortive, subclinical, or latent infections (Ruegsegger, Black & Sharpless 1961;Bell 1966Bell , 1975, localized (intramuscular) replication of the virus (Baer 1975b), ingestion of infected material (Ramsden & Johnston 1975), or bite exposure (Serokowa 1969).…”
Section: Immune Responsementioning
confidence: 99%
“…Abortive rabies infection associated with rabies virus has been described previously in North America in raccoon hunters, fox trappers, veterinary college staff and students, and speleologists. [5][6][7] ABLV has caused abortive infections in dogs, cats and bats. 8 Confirmation of positive titres using two tests (RFFIT and ELISA) adds more weight to the results being a true positive.…”
Section: Antibodies To Australian Bat Lyssavirus In An Asymptomatic Bmentioning
confidence: 99%
“…These avian embryo vaccines are free of brain tissue and thus of the risk of inducing paralytic accident (see below). The HEP (high egg passage Flury) vaccine (Fox et al, 1957;Sharpless et al, 1957;Ruegsegger et al, 1961), made in the same way as the Flury canine (low egg passage) vaccine, has been widely used for prophylactic vaccination. Although HEP is a live virus vaccine, the virus does not multiply in man and the response depends only on the antigen mass administered.…”
Section: Vaccines Used In Manmentioning
confidence: 99%
“…veterinarians and their assistants in enzootic areas. Ruegsegger et al (1961) found that with even the best schedule of doses, HEP vaccine produced anitbody in 80-90 per cent of recipients. Atanasiu et al (1961) showed that antibody responses were best when there was an interval of 20 days between two of the doses.…”
Section: Prophylactic Vaccinationmentioning
confidence: 99%